2021
DOI: 10.3390/biology10020102
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Effectiveness of Chitosan as a Biofunctionalizer of Titanium Implants

Abstract: Chitosan is a natural polysaccharide extracted from the shells of crustaceans that has been proposed as a scaffold in tissue engineering. Certain studies have proven a greater osseointegration of titanium surfaces that are functionalized with chitosan. The MEDLINE, CENTRAL, PubMed, and Web of Science databases were electronically searched for in vivo studies. Seven studies met the inclusion criteria. Animal models, implant site, chitosan incorporation methods, and methods of analysis were emphasized. The selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…A chitosan/dicarboxylic acid scaffold was shown in vivo to be an effective bone regeneration material with good osteoinductive and osteoconductive properties [26]. In a review paper, titanium surfaces functionalized with chitosan were concluded to have greater osseointegration capacity than uncoated controls [27]. Thitiset et al [28], used chitoologosaccharide for preparation of composites that did show promising results in cell culture, as well as for new bone formation in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…A chitosan/dicarboxylic acid scaffold was shown in vivo to be an effective bone regeneration material with good osteoinductive and osteoconductive properties [26]. In a review paper, titanium surfaces functionalized with chitosan were concluded to have greater osseointegration capacity than uncoated controls [27]. Thitiset et al [28], used chitoologosaccharide for preparation of composites that did show promising results in cell culture, as well as for new bone formation in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, its high biocompatibility, hydrophilicity and biodegradability, in addition to being non-toxic ( Tajdini et al, 2010 ), are noteworthy. For all these reasons, its ability to increase cell adhesion and protein adsorption in Ti coatings has been highlighted, which would be beneficial for improving the osseointegration of dental implants ( Bumgardner et al, 20032003 ; Bumgardner et al, 2003 ; López-Valverde et al, 2021 ). Muzzarelli et al ( Muzzarelli et al, 1994 ) demonstrated in a clinical trial on 10 patients, bone neoformation and mineralization of post-extraction sockets, due to the cationic nature and chelating ability of Cht; these results would highlight the potential of Cht coatings to support and facilitate osseointegration of orthopedic and craniofacial implants.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these considerations, the hydrophobic QRC could be embedded into NLCs and co-administered with the watersoluble CPX by preparing a multifunctional polymeric system. In this context, chitosan (CTS) could be the best polymer to be chosen as it is a natural water-soluble (pH ≈ 6.4, below its pKa) polysaccharide derived from the partial deacetylation of chitin found in crustaceans' exoskeletons, insects, and fungi cell walls [41,42]. CTS consists of N-acetylglucosamine and D-glucosamine units and its physico-chemical properties depend on its molecular weight and degree of deacetylation [43,44].…”
Section: Introductionmentioning
confidence: 99%
“…CTS consists of N-acetylglucosamine and D-glucosamine units and its physico-chemical properties depend on its molecular weight and degree of deacetylation [43,44]. Moreover, CTS is a biocompatible, biodegradable, and non-toxic polymer featuring biological activities that make it an antioxidant, mucoadhesive, and broad-spectrum antimicrobial polysaccharide [41,42]. The mechanism of action of CTS relies on the interaction between its NH 3 + groups and the negatively charged moieties of the bacterial cell wall, which ultimately leads to cell lysis [43].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation